2018
DOI: 10.3389/fmats.2018.00071
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Exceptional Passivation Effect of 0.8 nm Evaporated Aluminium on Transparent Copper Films

Abstract: Slab-like copper films with a thickness of 9 nm (∼70 atoms) and sheet resistance of ≤9 sq −1 are shown to exhibit remarkable long-term stability toward air-oxidation when passivated with an 0. 8 nm aluminium layer deposited by simple thermal evaporation. The sheet resistance of 9 nm Cu films passivated in this way, and lithographically patterned with a dense array of ∼6 million apertures per cm 2 , increases by <3.5% after 7,000 h exposure to ambient air. Using a combination of annular-dark field scanning tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…It is evident from Figure that using a mixed APTMS/MPTMS seed layer reduces the rate of oxidation of a 9 nm Cu film on glass by a factor of 4 from 0.0198 to 0.0048 Ω sq −1 hr −1 . This large improvement in stability can be rationalized in terms of the more compact slab‐like structure of the Cu film deposited onto seed layer modified glass, which impedes the diffusion of oxygen along the grain boundaries between crystallites …”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…It is evident from Figure that using a mixed APTMS/MPTMS seed layer reduces the rate of oxidation of a 9 nm Cu film on glass by a factor of 4 from 0.0198 to 0.0048 Ω sq −1 hr −1 . This large improvement in stability can be rationalized in terms of the more compact slab‐like structure of the Cu film deposited onto seed layer modified glass, which impedes the diffusion of oxygen along the grain boundaries between crystallites …”
Section: Resultsmentioning
confidence: 98%
“…We have previously shown that a mixed molecular monolayer of MPTMS and APTMS co‐deposited from the vapour phase is an effective seed layer for the formation of Cu films on both glass and plastic substrates ,. APTMS catalyses the coupling reaction with the substrate, while both APTMS and MPTMS bind strongly to the incoming Cu atoms as they arrive at the substrate resulting in more slab‐like film formation and vastly improved film quality at <10 nm ,,,. Using this approach the surface roughness of a 9 nm evaporated Cu film on glass is reduced from 1.44±0.12 to 1.02±0.05 nm and the initial sheet resistance is reduced from 13.8 to 10.8 Ω sq −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations